ASSOCIATION BETWEEN NUTRITIONAL STATUS AND THE OUTCOME OF PEDIATRIC PATIENT WITH DENGUE SHOCK SYNDROME - Shidi Laras Pramudito; Dewi Ratna Sari; Ninik Asmaningsih Soemyarso (Universitas Airlangga, Surabaya, Indonesia, 2020)
Background: The association between nutritional status and dengue infection is still considered controversial. Researches that study obesity and shock in pediatric patients with dengue hemorrhagic fever (DHF) has been widely carried out. However, researches that study the association between obesity and the outcome of patients with dengue shock syndrome (DSS) are still rarely done. Objective: The objective was to study the association of obesity in body mass index-for-age (BMI-for-age), gender, and age to the outcome of patients with dengue shock syndrome (recurrent shock or death). Materials and Methods: The research was analytical retrospective observational research with a case-control design using secondary data from the medical records of pediatric patients with DSS in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia during 2015. The analyses used to test the association of obesity (BMI-for-age), gender, age and the outcome of patients with dengue shock syndrome (recurrent shock or death) were the Chi-Square or Fisher Exact test. Results: The sample acquired was 60 data, consisting of 46 patients with DSS without recurrent shock or death and 14 pediatric patients with DSS experiencing recurrent shock or mortality. The frequency of boys and girls were found in equal numbers. Age group >5-10 years was found more common (45%). The results of the analyses test found no association between gender (p=0.542), age (p=0.314), and obesity (p=1.000) and the outcome of pediatric patients with dengue shock syndrome. Conclusion: There were no association found between obesity, age, and gender to the outcomes of pediatric patients with DSS at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.